PENGARUH RASIO KEUANGAN TERHADAP LABA PT BANK RAKYAT INDONESIA TBK - Longginus Gelatan (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2020)
The purpose of this study is to analyze the effect of CAR, NIM, LDR and BOPO on PT Bank Rakyat Indonesia Tbk's profit. This research is an associative research analyzed with multiple linear regression analysis. The data used is the data of financial ratios and profit for the period 2003 to 2019. The results showed that there was a significant effect between CAR on profit with the direction of positive influence, which means that if there was an increase in CAR, BRI's profits would increase. There is a significant influence between NIM on profit with negative influence direction, which means if there is an increase in NIM, BRI's profit will decrease. There is a significant influence between the LDR on profit with the direction of a positive influence which means that if an LDR increases, BRI's profit will increase. While the influence of BOPO on profit there is no significant effect.